Software para la gestión de monitorias académicas de los estudiantes de la Universidad Autónoma de Occidente. (2022)
The Universidad Autónoma de Occidente, in its mission to contribute to the generation of knowledge and construction of integral people, starts with the use of teaching methodologies by teachers, who are responsible for motivating the entire student community to continue with their aspirations to become future professionals. In order to achieve the objectives of the institution, the following is the development and implementation of a software system for the management of monitoring, tutoring and academic advising of students of the Universidad Autónoma de Occidente, which aims to optimize and improve the processes of continuous academic monitoring of students of the institution. During the development of this software, a series of activities were planned under the cascade methodology, which began with the stage of analysis and identification of needs of the process of monitoring, tutoring and counseling of the Universidad Autónoma de Occidente, this stage was accompanied by members of the university community who are within the process of academic support to students of the institution. Subsequently these needs became requirements and use cases which were vital in the following stages of software development, among which are the database design, architecture and prototypes. To finally reach the stages of development and integration of components and thus validate the correct operation through functional testing and integration